Determinan minat karir mahasiswa akuntansi dengan penghargaan finansial sebagai moderasi - Anastasia, Vivian; Kurniawan, Rudy; Muhsin, Muhsin (Akuntansi dan Teknologi Informasi, 2025)
Purpose – this study intend to examine and analyze the factors that may influence accounting students' career interest by adding a moderating effect in the form of financial rewards. Methods – This study uses a quantitative approach with purposive sampling. The population consists of 332 accounting students enrolled in 2022, and the sample includes 181 students. The analytical tool used is Warp PLS 8.0. Findings - This study found a significant influence of job market considerations, social values, and work environment on accounting students' career interest. but, if moderating effect added is financial rewards, not all variable can be moderated by it. Financial rewards proven strengthen the influence of job market considerations and work environment on students' career interest, but were not able to strengthen or weaken the influence of social values on accounting students's career interest. Implications - This study can provide a theoretical contribution that supports the Theory of Planned Behavior and Expectancy Theory, which state that career choices are influenced by social attitudes, subjective norms, and perceived control. Originality - This study combines variables from two previous studies by adding a moderating effect in the form of financial rewards.